Spiritual Values and Spiritual Practices: Interactive Effects on Leadership Effectiveness - Zakiyulfikri Ali; Muhammad Zaky (ETIKONOMI, 2018)
The relationship between spirituality and leadership effectiveness has been discussed over decades. These relations have been separated in two big perspective—first, an esoteric realm of intangible ideas and emotions; and second, a practical area and scientific inquiry. This research tries to integrate these two different perspectives. Specifically, this research examines the effects of spiritual values and spiritual practices on leadership effectiveness. The findings indicate that spiritual values and spiritual practices have positive effects on leadership effectiveness. This research also shows that spiritual values and spiritual practices have interactive effects on leadership effectiveness. This result implies that organizations should enhance the spiritual values and practices. Discussion, practical, and theoretical implications for further researches are offered. DOI: 10.15408/etk.v17i1.6497